Draft genome sequence of a rare pigmented mycobacterium avium subsp. paratuberculosis type C strain - Barbosa, Pedro (2017)
Mycobacterium avium subsp. paratuberculosis is the causative agent of paratuberculosis. We report here the draft genome sequence of a rare pigmented M. avium subsp. paratuberculosis type C strain, comprising 58 contigs and having a genome size of 4,851,414 bp. The genome will assist in the execution of pigmentation and virulence studies on this mycobacterium.